The electrolyte-layer free fuel cell using a semiconductor-ionic Sr2Fe1.5Mo0.5O6-δ – Ce0.8Sm0.2O2-δ composite functional membrane. (28th September 2017) - Deng, Hui; Feng, Chu; Zhang, Wei; Mi, Youquan; Wang, Xunying; Dong, Wenjing; Wang, Baoyuan; Zhu, Bin
Abstract: Commercial double Perovskite Sr2 Fe1.5 Mo0.5 O6-δ (SFM), a high performance and redox stable electrode material for solid oxide fuel cell (SOFC), has been used for the electrolyte (layer) -free fuel cell (EFFC) and also as the cathode for the electrolyte based SOFC in a comprehensive study. The EFFC with a homogeneous mixture of Ce0.8 Sm0.2 O2-δ (SDC) and SFM achieved a higher power density (841 mW cm −2 ) at 550 °C, while the SDC electrolyte based SOFC, using the SDC-SFM composite as cathode, just reached 326 mW cm −2 at the same temperature. The crystal structure and the morphology of the SFM-SDC composite were characterized by X-ray diffraction analysis (XRD), and scanning electron microscope (SEM), respectively. The electrochemical impedance spectroscopy (EIS) results showed that the charge transfer resistance of EFFCs were much lower than that of the electrolyte-based SOFC. To illustrate the operating principle of EFFC, we also conducted the rectification characteristics test, which confirms the existence of a Schottky junction structure to avoid the internal electron short circuiting. This work demonstrated advantages of the semiconductor-ionic SDC-SFM material for advanced EFFCs. Highlights: The EFFC with 40 wt% SFM reached 841 mW cm −2  at 550 °C. The EFFC has a much lower Rct than the electrolyte based SOFC. The EFFC with Schottky junction shows high OCV and much less resistance.